2021
DOI: 10.1016/j.waojou.2021.100593
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and temporal trends of food allergy among preschool children in Northern Thailand between 2010 and 2019

Abstract: Background: Although recent studies suggest that the prevalence of food allergy (FA) has not changed, the data from developing countries are limited. This study aimed to investigate time trends in the prevalence of FA among preschool children in 2010 and 2019 in Northern Thailand.Methods: Two cross-sectional studies were performed, 9 years apart (2010 and 2019), using the same methods, in children aged 3-7 years living in Chiang Mai, Thailand. Parent-reporting questionnaire surveys were conducted. Families wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…On the other hand, a register‐based study on any food allergy diagnosis found no association with birth order ≥2 versus 1 53 . Similarly, Of the two population‐based studies on sibship size and any food allergy, one indicated a lower risk of the outcome in subjects with ≥6 versus <6 siblings, 54 while the other reported no significant association 55 …”
Section: Resultsmentioning
confidence: 94%
“…On the other hand, a register‐based study on any food allergy diagnosis found no association with birth order ≥2 versus 1 53 . Similarly, Of the two population‐based studies on sibship size and any food allergy, one indicated a lower risk of the outcome in subjects with ≥6 versus <6 siblings, 54 while the other reported no significant association 55 …”
Section: Resultsmentioning
confidence: 94%
“… 16 However, the pattern of food allergy seen in our study has important differences with other Asian countries as well as with Europe and the United States ( Table 5 ). 5 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 …”
Section: Discussionmentioning
confidence: 99%
“…Jackfruit was uncommonly studied and sensitization to jackfruit on SPT was 2.46% in children from India 9 . One study from Thailand observed self‐reported adverse reactions to insect eggs (Ant) of 0.53% in children 36 (Figure 6).…”
Section: Variation In Foods Associated With Food Allergy In India Whe...mentioning
confidence: 99%
“…40 The highest self-reported adverse reaction to shellfish (24.4%) was observed in China. 32 Self-reported adverse reactions to the most common foods of global relevance in children and adults from India and other LMIC countries from Europe, 13,14 North America, 21,22 South America, 23,24 and Asia 18,19,[25][26][27][28][29][31][32][33][34][35][36][37][38] are presented as a heatmap (Figure 5A).…”
Section: Common Food Allergensmentioning
confidence: 99%
See 1 more Smart Citation